Influence of plume attenuation under high power laser welding of copper using visible wavelengths - Ermer, Jakob; Maier, Andreas; Schmidt, Michael; Kaufmann, Florian; Roth, Stephan (Journal of Laser Applications, 2021)
Joining of copper materials has become a key factor in laser material processing of electric components like electric engines, batteries, or power electronics. A paramount challenge is the design of the laser welding process, which has to fulfil the requirements of high energy efficiency and highest seam quality at the same time. By now, high-power laser beam sources emitting visible laser radiation are available to promote the well-suited noncontact joining method, which is furthermore characterized by local energy input and high automation potential. These laser sources can now face the challenges of welding highly conductive and reflective materials, such as copper, which originate mainly in the low absorption of conventionally used infrared wavelengths at room temperature and the rapid jump of absorptivity at transition from solid to liquid state. An increase in absorption of electromagnetic radiation to more than 40% for copper at room temperature for λ = 515 nm leads to increasing energy input in the material and promotes a more efficient process therefore. However, up to now, mostly the heat conduction welding regime has been examined and the effects of shorter wavelengths on deep penetration welding have not been understood in detail. A strong deviation in weld seam depth between infrared and green laser radiation is observed for identical process parameters depending on the use of additional gas supply [F. Kaufmann, A. Meier, J. Ermer, S. Roth, and M. Schmidt, “Influence of defocusing in deep penetration welding of copper by using visible wavelength,” in Proceedings of the Eleventh International WLT-Conference on Lasers in Manufacturing, Munich, 21-24 June 2021 (M. Reth, Munich, 2021)]. Consequently, radiation attenuation by the metal vapor inside and above the keyhole plays a substantial role in the case of 515 nm laser welding [M. Haubold, A. Ganser, T. Eder, and M. F. Zäh, “Laser welding of copper using a high power disc laser at green wavelength,” Procedia CIRP 74, 446-449 (2018)]. In this work, we investigate in situ measurements of plume attenuation during laser beam welding of copper with 515 and 1030 nm laser beam sources. Both laser sources are equipped with comparable optical setups to achieve identical focal diameters on the material surface. We investigate the plume characteristics in the deep penetration welding mode of copper. A range of industry-relevant process parameters are investigated to create a basis for comparison with theoretical models. It is found that a significant difference in the attenuation of both laser wavelengths occurs in the case of deep penetration welding copper specimen and blowing the vapor plume out of the beam path is recommended therefore for an efficient welding process.
CRIS-Team Scopus Importer:2021-10-01